2020
DOI: 10.1136/gpsych-2020-100259
|View full text |Cite
|
Sign up to set email alerts
|

Psychological impact of the COVID-19 pandemic on healthcare workers: a cross-sectional study in China

Abstract: BackgroundHealthcare workers fighting against the coronavirus disease 2019 (COVID-19) pandemic are under tremendous pressure, which puts them at an increased risk of developing psychological problems.AimsThis study aimed to investigate the prevalence of psychological problems in different healthcare workers (ie, physicians, medical residents, nurses, technicians and public health professionals) during the COVID-19 pandemic in China and explore factors that are associated with the onset of psychological problem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

47
422
17
40

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 444 publications
(576 citation statements)
references
References 42 publications
47
422
17
40
Order By: Relevance
“…The results of the analysis also showed that the prevalence of sleep disturbances in physicians is higher than nurses. Nevertheless, this was not consistent with most of the existing studies [16,25,26]. On the other hand, the results of the study by Wang et al (2020) [27] were consistent with our finding.…”
Section: Discussioncontrasting
confidence: 89%
See 2 more Smart Citations
“…The results of the analysis also showed that the prevalence of sleep disturbances in physicians is higher than nurses. Nevertheless, this was not consistent with most of the existing studies [16,25,26]. On the other hand, the results of the study by Wang et al (2020) [27] were consistent with our finding.…”
Section: Discussioncontrasting
confidence: 89%
“…All collected pieces of research had used self-reporting questionnaires. The Sleep disturbances Severity Index (ISI) questionnaire was used in 3 studies [16,25,26], the other 3 studies used the Pittsburgh Sleep Quality Index (PSQI) questionnaire [27][28][29] and the Athens Sleep disturbances Scale (AIS) questionnaire was used in one study [24]. Further characteristics and information related to these studies are provided in Table 2.…”
Section: Google Scholarmentioning
confidence: 99%
See 1 more Smart Citation
“…Psychological symptoms including anxiety, depression, insomnia are prevalent in up to 60 % among physicians, nurses and medical residents during Covid-19 pandemic ( Que et al;, 2020 ), which are likely to persist for several years. HCP who worked in respiratory medicine during the SARS outbreak in 2003 had persistent and significantly greater level of psychological symptoms including anxiety, depression and post-traumatic stress symptoms a year later ( McAlonan et al, 2007 ).…”
Section: Mental Health Impact On Frontline Healthcare Professionals (mentioning
confidence: 99%
“…However, apart from doctors, people working in healthcare facilities such as nurses, ward staff, cleaning staff, porters, and administrative staff are also variably vulnerable 23 and might face mental health problems. People working in certain specialties such as a respiratory ward, infectious diseases ward or critical care ward are subject to greater risk and might be under greater stress.…”
Section: Introductionmentioning
confidence: 99%